Sensory nerve action potentials and sensory perception in women with arthritis of the hand - Calder, Kristina M (BioMed Central, 2012)
BACKGROUND: Arthritis of the hand can limit a person’s ability to perform daily activities. Whether or not sensory deficits contribute to the disability in this population remains unknown. The primary purpose of this study was to determine if women with osteoarthritis (OA) or rheumatoid arthritis (RA) of the hand have sensory impairments. METHODS: Sensory function in the dominant hand of women with hand OA or RA and healthy women was evaluated by measuring sensory nerve action potentials (SNAPs) from the median, ulnar and radial nerves, sensory mapping (SM), and vibratory and current perception thresholds (VPT and CPT, respectively) of the second and fifth digits. RESULTS: All SNAP amplitudes were significantly lower for the hand OA and hand RA groups compared with the healthy group (p < 0.05). No group differences were found for SNAP conduction velocities, SM, VPT, and CPT. DISCUSSION: We propose, based on these findings, that women with hand OA or RA may have axonal loss of sensory fibers in the median, ulnar and radial nerves. Less apparent were losses in conduction speed or sensory perception.